Evidence for a transgenerational mutational signature from ionizing radiation exposure in humans - Fabian Brand; Hannah Klinkhammer; Alexej Knaus; Manuel Holtgrewe; Leonie Weinhold; Dieter Beule; Kerstin Ludwig; Prachi Kothiyal; George Maxwell; Markus Noethen; Matthias Schmid; Karl Sperling; et al. (Scientific Reports)
Abstract The existence of transgenerational effects of radiation exposure on the human germline remains controversial. Evidence for transgenerational biomarkers are of particular interest for populations, who have been exposed to higher than average levels of ionizing radiation (IR). This study investigated signatures of parental exposure to IR in offspring of former German radar operators and Chernobyl cleanup workers, focusing on clustered de novo mutations (cDNMs), defined as multiple de novo mutations (DNMs) within 20 bp. We recruited 110 offspring of former German radar operators, who were likely to have been exposed to IR (Radar cohort, exposure = 0–353 mGy), and reanalyzed sequencing data of 130 offspring of Chernobyl cleanup workers (CRU, exposure = 0–4080 mGy) from Yeager, et al. In addition, we analyzed whole genome trio data of 1275 offspring from unexposed families (Inova cohort). We observed on average 2.65 cDNMs (0.61 adjusted for the positive predictive value (PPV)) per offspring in the CRU cohort, 1.48 (0.34 PPV) in the Radar cohort and 0.88 (0.20 PPV) in the Inova cohort. Although under the condition that the proportion of true mutations is low in this analysis, this represented a significant increase ( $$\:p<0.005$$ ) of cDNMs counts, that scaled with paternal exposure to IR ( $$\:p<0.001$$ ). Our findings corroborate that cDNMs are a potential transgenerational biomarker of paternal IR exposure.